"What's mine?" : rural women's experiences around property rights in the context of dissolved marriages in matrilineal societies : a case study of Muluwila Village in Kuntunmanje area, Zomba District, malawi. - Matinga, Bridget (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.